ПОНЯТТЯ ТА ОЗНАКИ АДМІНІСТРАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ ПІДПРИЄМНИЦЬКОЇ ДІЯЛЬНОСТІ - Димидюк, Катерина Дмитрівна (SUPREMANCE OF LAW, 2017)
The article is devoted to the study of administrative and legal regulation of entrepreneurial activity. Based on the theoretical developments of administrative scientists and analyzing the doctrinal provisions regarding the interpretation of such concepts, in particular, as: «entrepreneurship»; «entrepreneurship»; «object of administrative and legal regulation»; «administrative and legal regulation», the authors definition of the concept of «administrative and legal regulation of business activity» is proposed in the article. It is substantiated that social relations between subjects of entrepreneurial activity and subjects of public activity are the subject of study of the science of administrative law, and entrepreneurial activity is the object of the influence of administrative and legal regulation. The author’s defi nition of the concept of «entrepreneurial activity» is proposed and its essence is revealed, as one of the types of independent economic activity implemented by an individual or legal entity at its own risk, which is carried out at the expense of own or borrowed funds, and aims to obtain profit or other social benefits . The definition of the concept of «Administrative and legal regulation of business activity» is proposed and its content is revealed. The essence of enforcement of court decisions and decisions of other bodies as one of the types of administrative activity is disclosed. The main features of administrative and legal regulation of entrepreneurial activity as one of the types of regulatory influence on social relations in the specified sphere are given.